E-LEARNING AND ONLINE EDUCATION IN THE DIGITAL ERA - Muratova Dinara Timurovna (Journals Park Publishing, 2026)
The rapid digitalization of modern society has significantly transformed the structure and philosophy of education. Over the last decade, e-learning and online education have shifted from being supplementary instructional tools to becoming strategic pillars of global educational systems. This research explores the evolution, pedagogical foundations, advantages, challenges, and long-term implications of digital learning in the contemporary era.
Keywords: Digital transformation, e-learning, online education, blended learning, ICT, digital pedagogy.